Puget Sound Navigation Company steamer GEORGE E. STARR at the dock in Seattle, before 1911 (1906)
Cargo from the Northern Pacific Railroad Company and the Pennsylvania Lines in the background PH Coll 794.43 The GEORGE E. STARR was built in 1879 at the J.F.T. Mitchell shipyard in Seattle for the Puget Sound Steam Company's Seattle-Victoria route. She was a wooden passenger sidewheel steamer, 148 feet long by 28 feet in beam. She had a single-cyliner beam engine. The vessel alternated between various routes, particularly the Victoria, Blaine, Whatcom, Anacortes, and Fairhaven routes. In 1911, the Puget Sound Company disposed of the STARR, the last sidewheel steamer in its fleet. Although there were initial plans for further service in British Columbia, she was abandoned in Lake Union. Other noteable services included a brief stint on the Astoria - Ilwaco route in 1982 and service as a transport between Seattle and Skagway during the Klondike Gold Rush. (Source: Newell, Gordon, ed. "The H.W. McCurdy Marine History of the Pacific Northwest." Seattle: The Superior Company, 1966.) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number